2019
DOI: 10.1111/jvim.15497
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for recurrence of endocrinopathic laminitis in horses

Abstract: Background Endocrinopathic laminitis is common in horses and ponies, but the recurrence rate of the disease is poorly defined. Objectives To determine the incidence of, and risk factors for, the recurrence of endocrinopathic laminitis. Animals Privately owned horses and ponies with acute laminitis (n = 317, of which 276 cases with endocrinopathic laminitis were followed up to study completion). Methods This prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Endocrinopathic laminitis is common in horses and ponies, but the recurrence rate of the disease is poorly defined. The recurrence rate for endocrinopathic laminitis was 34.1% (23).…”
Section: Discussionmentioning
confidence: 93%
“…Endocrinopathic laminitis is common in horses and ponies, but the recurrence rate of the disease is poorly defined. The recurrence rate for endocrinopathic laminitis was 34.1% (23).…”
Section: Discussionmentioning
confidence: 93%
“…Determining the reasons for slow improvement and/or recurrence is particularly important, as these are associated with a high euthanasia rate [1]. A recent survey indicated that factors such as a previous history of laminitis and the degree of insulin dysregulation are predictive of laminitis recurrence [22], and further detailed investigations are currently underway to determine the association of these and other factors with improvement rates. Our observation that weight shifting had a lower prevalence (64%) on the day of diagnosis than the locomotive criteria and digital pulse (98-100%), is similar to that seen in an earlier study [2].…”
Section: Discussionmentioning
confidence: 99%
“…Laminitis can occur due to any number of systemic or local insults and appear as an acute or chronic form [ 283 , 284 , 287 , 292 , 293 , 294 ]. The most common and known aetiologies for laminitis include endocrinopathies, sepsis/endotoxemia and overloading (supporting limb laminitis due to injury of the contralateral limb) [ 283 , 284 , 285 , 287 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 ].…”
Section: Regenerative Therapies By Disease Areamentioning
confidence: 99%